2023
DOI: 10.1186/s12931-023-02317-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional respiratory impairment and related factors in patients with interstitial pneumonia with autoimmune features (IPAF): Multicenter study from NEREA registry

Abstract: Background The objective of the present study is to describe the characteristics of interstitial pneumonia with autoimmune features (IPAF) patients, to assess the incidence rate of functional respiratory impairment over time and to evaluate the influence of therapeutic alternatives on the prognosis of these patients. Methods A longitudinal observational multicenter study was performed (NEREA registry). It was carried out by a multidisciplinary tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…While immunosuppression was associated with increased mortality in IPF, immunosuppressive treatment was found to improve pulmonary functions in UIP associated with RA and CTD-ILD [43][44][45]. Similar results were also obtained in IPAF patients: treatment with Micophenolate Mofetil and Prednisone was associated with non-progression in IPAF patients, even controlling for the presence of a radiological pattern of UIP [46,47]. Recently, Yamano Y et al reported an interesting study on histologically proven UIP-IPAF patients, comparing the treatment of these patients [48].…”
Section: Discussionmentioning
confidence: 78%
“…While immunosuppression was associated with increased mortality in IPF, immunosuppressive treatment was found to improve pulmonary functions in UIP associated with RA and CTD-ILD [43][44][45]. Similar results were also obtained in IPAF patients: treatment with Micophenolate Mofetil and Prednisone was associated with non-progression in IPAF patients, even controlling for the presence of a radiological pattern of UIP [46,47]. Recently, Yamano Y et al reported an interesting study on histologically proven UIP-IPAF patients, comparing the treatment of these patients [48].…”
Section: Discussionmentioning
confidence: 78%
“…The effectiveness of these drugs has been proved by several clinical trials. In some studies, the action of these molecules resulted in improvements when associated with immunosuppressants [36], although it should be noted that the treatment with immunosuppressants in IPF was also associated with an increased risk of acute exacerbation (AE) [37]; however, UIP-IPAF patients had significant benefit from the immunosuppressive treatment, despite the fact that the nuanced clinical picture did not allow for a specific classification as an autoimmune disease [30,38,39]. One of the current unmet needs for the coming years is the recognition of a subgroup of UIP patients who may have benefited from combined treatment with immunosuppressants and antifibrotics.…”
Section: Discussionmentioning
confidence: 99%